Aplicação de energia eletromagnética na região do infravermelho para a secagem de sementes de Moringa oleifera Lam. - Ferreira, Camila Felix (2015)
Moringa seeds (Moringa oleífera) have received special attention because of the potential to be applied as natural coagulant in water treatment, as well as source for biodiesel production, due to high quality of the oil contained within them. However, they also have high moisture content, requiring to be submmitted to drying process. Aiming to contribute with P, D & I of energy saving dryers to this seed specie, this work had as main objective to evaluate the potential use of infrared radiation for drying seeds from Moringa oleífera Lam, through an experimental study involving the determination of drying kinetics, the shrinkage characterization, the evaluation of energy consumption as well as of the process effects on the product quality. Drying tests were performed at IR source temperatures of 90, 120 e 160°C. Image analysis was employed to quantify particles shrinkage during drying. IR drying of moringa seeds was accompanied by reductions of particles volume and surface area, which were found to be dependent only from dimensionless moisture and seed structure (with and without seed coat). The IR drying behavior of the material was characterized by the presence of three drying periods: heating up, constant moisture flux and falling moisture flux. This latter was predominant in all investigated conditions, indicating that diffusion controls the drying process. Neglecting shrinkage of kernel during IR drying led to an erroneous shortening of the constant flux period and overestimation of the mass transfer by diffusion. The shell that coats the seeds has limited the volume contraction of particle (10%), when compared to the shrinkage of unshelled seeds or kernels (60%), thus contributing to the development of a porous structure within the particle. Although the shell acts as a resistance to mass and heat transfer, mainly in initial stages of drying, the time required for the seed to reach the target moisture was not significantly different from that verified for the kernels. The specific energy consumption was in the range 36,4 a 45,8 MJ kg-1 evaporated water for seeds with tegument and 38,7 a 46,5 MJ kg-1 for seeds without tegument. All IR-dried samples presented physiological viability, according to tetrazolium test. The total changes in product color indicated that the seeds were more susceptible to degradation of their components and browning after shell removal, being recommended that in long processes final material temperature does not reach values higher than 40oC, or is submitted to rapid drying conditions. An overall analysis based on the combination of product quality, mass transfer and energy consumption aspects has indicated the IR heating temperature of 160oC as the optimum condition to fast and efficiently reduce the moisture to levels considered safe for storage, preserving quality attributes of the product. Regarding the influence of shell, it is not needed to peel the seeds before drying, leading to non-time consuming process, also avoiding additional costs with a pre - treatment step of the material.